2014
DOI: 10.1111/bjet.12174
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding split attention in computer‐based testing: Is neglecting additional information facilitative?

Abstract: This study investigated whether design guidelines for computer-based learning can be applied to computer-based testing (CBT). Twenty-two students completed a CBT exam with half of the questions presented in a split-screen format that was analogous to the original paper-and-pencil version and half in an integrated format. Results show that students attended to all information in the integrated format while ignoring information in the split format. Interestingly, and contrary to expectations, they worked more ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 49 publications
(50 reference statements)
0
43
0
3
Order By: Relevance
“…Sweller et al (1998) proposed that working memory capacity can be filled with three types of loads, namely load caused by active processing of the information (germane load), load stemming from the difficulty of the task (intrinsic load), and by load stemming from other unnecessary cognitive processes that do not contribute to executing the task at hand (extraneous load). The amount of cognitive load posed upon working memory (i.e., mental effort) can be measured with different methods, such as subjective rating scales (Paas, 1992) or silent pauses in thinking aloud (Yin & Chen, 2007;Jarodzka, Janssen, Kirschner, & Erkens, 2015).…”
Section: Basic Assumptions Of Learning With Multimediamentioning
confidence: 99%
“…Sweller et al (1998) proposed that working memory capacity can be filled with three types of loads, namely load caused by active processing of the information (germane load), load stemming from the difficulty of the task (intrinsic load), and by load stemming from other unnecessary cognitive processes that do not contribute to executing the task at hand (extraneous load). The amount of cognitive load posed upon working memory (i.e., mental effort) can be measured with different methods, such as subjective rating scales (Paas, 1992) or silent pauses in thinking aloud (Yin & Chen, 2007;Jarodzka, Janssen, Kirschner, & Erkens, 2015).…”
Section: Basic Assumptions Of Learning With Multimediamentioning
confidence: 99%
“…printed text and pictures) is presented close together, so learners do not have to visually search for information in order to be able to integrate it. Interestingly, Jarodzka et al 27 did not find a positive effect of contiguity in a computer-based testing situation. Eye tracking was used to understand these findings.…”
Section: Use Of Eye Tracking To Investigate and Optimise Instructionamentioning
confidence: 93%
“…In these learning scenarios, eye-tracking data can aid researchers and educators in studying attention and shifts in attention underlying the split-attention effect. Past research has shown that under experimental conditions, learners focus on text; under naturalistic conditions, they focus on images, and when the information is appropriately integrated, then learners process it all (Jarodzka, Janssen, Kirschner, & Erkens, 2015). Moreover, eye-tracking data has shown that as learners increase their knowledge and expertise they tend to fixate faster on more relevant information Jarodzka, Scheiter, Gerjets, & Van Gog, 2010).…”
Section: Eye-tracking and Learning Technologiesmentioning
confidence: 99%